2003
DOI: 10.1080/09593330309385665
|View full text |Cite
|
Sign up to set email alerts
|

Substrate concentration‐independent aerobic granulation in sequential aerobic sludge blanket reactor

Abstract: The development of aerobic granules was studied in four column-type sequential aerobic sludge blanket reactors fed with different substrate concentrations ranging from 500 to 3000 mg l(-1) COD. Results showed that aerobic granules successfully formed in all reactors fed with different substrate concentrations, indicating that the formation of aerobic granules is independent of the substrate concentration. The granule size, roundness, compactness, physical strength, as well as cell surface hydrophobicity and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 27 publications
4
53
0
3
Order By: Relevance
“…A stable granular structure is dependent on the production of large Extracellular Polymeric Substances (EPS) by heterotrophic bacteria (Liu and Tay, 2004;Liu et al, 2003). Accordingly, the studies for the partial nitrification in aerobic granular sludge were mainly carried out under the presence of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A stable granular structure is dependent on the production of large Extracellular Polymeric Substances (EPS) by heterotrophic bacteria (Liu and Tay, 2004;Liu et al, 2003). Accordingly, the studies for the partial nitrification in aerobic granular sludge were mainly carried out under the presence of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, microbial EPS differs both in specifi city and metal-sorption capacity with only few functional groups potentially involved in cation-binding. In spite of all these constraints, the ease of application of purifi ed EPS and that in biofi lm, activated sludges or biogranules in bioremediation have demonstrated effi ciency in several studies which have led to a large number of reports favoring this approach [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Tay et al [8] studied the effect of OLR on the reactor performance and a moderate OLR was found to favour the development of stable aerobic granules. Liu et al [9] also studied the effect of substrate concentration on the formation, structure, and characteristics of aerobic granules and observed that granules can be successfully formed with influent COD concentrations from 500 to 3000 mg/l.…”
Section: Resultsmentioning
confidence: 99%